Neuroimaging evidence of gray and white matter damage and clinical correlates in progressive supranuclear palsy - Piattella, Maria Cristina; Upadhyay, N.; Bologna, M.; Sbardella, E.; Tona, F.; Formica, A.; Petsas, N.; Berardelli, A.; Pantano, P. (Journal of neurology, 2015)
To evaluate gray matter (GM) and white matter (WM) abnormalities and their clinical correlates in patients with progressive supranuclear palsy (PSP). Sixteen PSP patients and sixteen age-matched healthy subjects underwent a clinical evaluation and multimodal magnetic resonance imaging, including three-dimensional T1-weighted imaging and diffusion tensor imaging (DTI). Volumetric and DTI analyses were computed using SPM and FSL tools. PSP patients showed GM volume decrease, involving the frontal cortex, putamen, pallidum, thalamus and accumbens nucleus, cerebellum, and brainstem. Additionally, they had widespread changes in WM bundles, mainly affecting cerebellar peduncles, thalamic radiations, corticospinal tracts, corpus callosum, and longitudinal fasciculi. GM volumes did not correlate with WM abnormalities. DTI indices of WM damage, but not GM volumes, correlated with clinical scores of disease severity and cognitive impairment. The neurodegenerative changes that occur in PSP involve both GM and WM structures and develop concurrently though independently. WM damage in PSP correlates with clinical scores of disease severity and cognitive impairment, thus providing further insight into the pathophysiology of the disease.